1999
DOI: 10.1038/10100
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of caveolin-1 in meiotic cell-cycle progression in Caenorhabditis elegans

Abstract: mall invaginations called caveolae are present on the surface of many cells and are a form of glycosphingolipid-and cholesterol-enriched microdomains or rafts in the plasma membrane 1,2 . The main component of the caveolar coat is caveolin-1 (refs 3,4), a membrane protein of relative molecular mass (M r ) 21,000 (21K), which binds cholesterol 5 and can form highmolecular-mass homo-oligomers resistant to sodium dodecyl sulphate (SDS) 6,7 . Caveolin-1 has been implicated in signal transduction, but its function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 16 publications
7
54
1
Order By: Relevance
“…Of particular interest was the punctate nature of labelling which is most obvious in the VNC, this staining suggests possible localisation to synapses. A similar expression pattern with an anti-CAV-1 antibody was observed by Scheel (1999).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Of particular interest was the punctate nature of labelling which is most obvious in the VNC, this staining suggests possible localisation to synapses. A similar expression pattern with an anti-CAV-1 antibody was observed by Scheel (1999).…”
Section: Resultssupporting
confidence: 79%
“…The CAV-1 protein is equally similar to both caveolin-1 and caveolin-3 from mammals. Previous results (Scheel et al 1999) showed that cav-1 is expressed predominantly in the nervous system in adult worms; however, no neuronal function has been elucidated. To investigate the role of cav-1, we used fluorescently tagged proteins to elucidate the localisation of CAV-1.…”
Section: Introductionmentioning
confidence: 96%
“…Although membrane cholesterol and the effects of cholesterol depletion have not yet been tested in mammalian oocytes, caveolin and LDM may play a general role in gamete development and function. Caveolin-1 has been reported to be involved in meiotic cell cycle progression in the nematode Caenorhabditis elegans as indicated by RNA interference [40]. Ablation of caveolin-1 by RNA interference resulted in increased germ cell progression through meiotic development and increased egg laying by the injected hermaphrodite.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, antisense-mediated ablation of Cav-1 expression in NIH 3T3 cells causes sustained hyperactivation of the Ras-p42/44 MAPK cascade (Galbiati et al, 1998). Finally, RNA interference-based ablation of Cav-1 in Caenorhabditis elegans leads to progression of the meiotic cell cycle, a phenotype that mirrors that of Ras activation (Scheel et al, 1999).…”
Section: Cav-1 Null Mammary Glands Show Premature Activation/hyperphomentioning
confidence: 97%